Best Practices on Islamic Values Integration at Madrasah English Classes: Teachers’ Practices in Contextualizing The Values - Galuh Nur Rohmah; Ulil Fitriyah; Lina Hanifiyah (JEELS (Journal of English Education and Linguistics Studies), 2019)
The idea of integrating Islamic values in non-religion subjects is still in the process of shaping its format. Many possibilities and flexibilities of the integration are existing and practiced by English teachers at Islamic Junior High School—knowingly as Madrasah Tsanawiyah (MTs). Also, in the middle of endless idea of integration, teachers have been trying to apply the integration based on their beliefs and situation. This study outlines the teachers’ best practices on integrating Islamic values in English lesson at MTs in Jawa Timur. By using descriptive qualitative method, this study portraits 6 English as Foreign Language (EFL) teachers’ best practices. Data were taken from classroom observation, interview, and documentation which then were analysed as best practices. Best practices refer to the practice of integration which is considered as working practice from each teacher’s situation. The situation was mostly influenced by teachers’ lack of confidence to contextualize and operationalize the values into the teaching materials and activities, and the lack of model for integration. Further study on how to operationalize the integration, and on developing the model of integration will be worth exploring.